Heterotaxy Polysplenia Syndrome in an Old Female - Hajri, Mohamed; Yangui, Maroua; Talbi, Ghofran; Ferjaoui, Wael; Farhat, Leila Ben; Bayar, Rached (Journal of Medicine, 2022)
Abstract not available J MEDICINE 2022; 23: 82-83